Metodologia de fixação das penas - Morais, Abel Cardoso (2002)
In this work are established objective criteria of fixation of the exclusive punishment of freedom and of fine, according to doctrinaire jurisprudencial orientation, and the Brazilian positive right. Target itself the first chapter to the panoramic analysis, to the study of the source, historical evolution and principles that govern the punishment. The second chapter cares for of the technical criteria of fixation of the exclusive feathers of freedom and of fine, boarding itself several referring aspects to dosage e of the penal sanction, such as: the fixation of the punishment-base, with strict observance of the judicial criteria; the establishment of the temporary punishment, considering the importance, extenuating and the contest among them; the determination of the definitive punishment, having in mind the punishment increase or decrease special causes, the contest among them and the logic of the calculation in the successive, there included causes those current of the tried crime, formal contest and continued crime, where not always the jurisprudence introduces a good solution inside the juridical technique. The fine punishment is treated under two variant: value of the days-fine’s day fine and quantity. The last chapter care for the judicial providences that happen to the fixation of the exclusive punishment of freedom and or fine, such as the substitution of prision or concession punishment of benefits. Each on of these benefits is studied of part the part, carryng itself in account the legal requisites that authorize the pertinence of one or of another, observing itself the current jurisprudence about the subject. They are examined the extrapenal effects of the condemnation, automatic and specific, like sanction form due to the penal condemnation. In the conclusive phase, they are selected the answers that were flushed in the context of the work and introduced suggestions.